An Atlas of the Hidradenitis Suppurativa Transcriptome - Weronika Szukala; Agata Lichawska-Cieslar; Piotr K. Krajewski; Maria Kulecka; Izabela Rumienczyk; Michał Mikula; Łukasz Matusiak; Jolanta Jura; Jacek C. Szepietowski (Adis, Springer Healthcare, 2024)
Abstract Introductions Hidradenitis suppurativa (HS) is a chronic inflammatory condition of the skin. Both genetic and environmental factors contribute to the risk of developing HS, but the pathogenesis of this disease is currently not fully understood. The aim of this study was to further current understanding of the molecular background of HS with the use of global transcriptome analyses. Methods Transcriptome profiling of perilesional and lesional skin of five patients with HS and six healthy control patients was performed by next-generation sequencing. Groups of differentially expressed genes characteristic of the skin of patients with HS were shortlisted by bioinformatic analysis. Results RNA sequencing followed by bioinformatic profiling revealed profound enrichment of inflammatory-related processes in both lesional and perilesional skin of patients with HS. There were, however, distinct differences in the gene expression profiles between the lesional and perilesional skin, with 1488 genes differentially expressed. Genes encoding typical proinflammatory cytokines were profoundly enriched within HS lesions. In contrast, those encoding mediators of extracellular matrix organization were highly expressed mostly in the perilesional area. Conclusions Our study provides novel insights into the mechanisms underlying the pathogenesis of HS, and the results also have potential clinical implications in both diagnosis and therapeutics.